Why Do Journalists Prefer Data Journalism? A Case Study of Online Journalists & Public Relations in UAE (Journal of Namibian Studies : History Politics Culture, 2023)
The new practices in journalism and news-making are adding every day. Consequently, data journalism adoption and usage are increasing today. This research also focuses on data journalism as one of the most considerable practices among PR& journalists in the United Arab Emirates. Theocratically supported by Audience Reception Theory; this study involves Structural Equation Modelling for data analysis purposes. Results revealed that Emirati journalists & Public relations departments much prefer using data journalism professionally (p> .000). For relevant purposes, these journalists perform data encoding by using the practical guide and rules for the encoding (p> .000) purposes. Besides, these journalists much prefer (p> .000) using graphs, charts, and other relevant data visualization approaches that further make data availability transparent and objective for the readers (p> .000). Finally, these journalists ensure easy and understandable data decoding among the audience, that may further lead to increase critical thinking among them (p> .000). Thus, it is concluded that Emirati journalists & PR are interested in readily adopting an applying the data journalism approaches not only to enhance their personal skills but also to provide the readers with the transparent data. The importance of data journalism also indicated the adoption of technology in traditional journalism as transforming the entire field where communication is based on a two-way approach. The researchers finally discussed the study limitations and made recommendations for future studies.